Nature as a Subject of Law in the Legal System of Uganda (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2021)
On 24 February 2019, the Parliament of Uganda approved the National Environment Act to provide for a correct management of the environment and natural resources. The Act was adopted in order to enhance the protection of the environment, address a strategic assessment in implementing environmental rights and sustainable development, and increase penalties for offences against nature. The relevance of this Act stands in the radical change of the legal consideration of the environment and nature. Indeed, the Ugandan legislation appears to alter the classical parameter of environmental law in considering Nature a subject entitled to its own rights with the possibility of recurring before the Courts in case of danger and/or violations. This reform marks a shift from an anthropocentric vision of the environment towards a more geocentric construction of environmental law.
Keywords: Environment; Climate Change; National Environment Act; Rights of Nature; Uganda